KOMPARASI PENYELESAIAN PENGADUAN NASABAH ANTARA BPD D.I. YOGYAKARTA DAN BPR DANAGUNG BAKTI GROUP - Rasyid Yuliansyah; Ani Yunita (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2018)
This study is determined how the settlement system of customer claims the Regional Development Bank of Yogyakarta and Danagung Bakti’s Rural Bank and its Legal Implications. This study is non-doctrinal or empirical. The type of the research is empirical research and the research approach is the law concept with data sources of primary data, secondary, and tertiary. Data was collected through interviews, and study literature or documents. The result of this study is the system settlement of Customer Complaints in Regional Development Bank of Yogyakarta and Danagung Bakti’s Rural Bank accordance with PBI Numb. 7/7/PBI/2005 as amended by Regulation Numb.10/10/PBI/2008 on settlement of Customer Complaints although the level of implementation in the field there are still some deficiencies. The legal implications concerning the existence of Standart Operating Procedure in the Regional Development Bank (BPD) of DIY result in the smooth implementation of the Customer Complaints Settlement process at Regional Development Bank DIY while the implications related to the absence of Standart Operating Procedure in Bank Perkreditan Rakyat Danagung Bakti cause still less optimal settlement process of customer complaint in Danagung Bakti Rural Bank.